Систематический обзор позднемиоценовых и раннеплиоценовых грызунов (Mammalia, Rodentia) Северного Причерноморья - Топачевский, В.А.; Скорик, А.Ф. (Вестник зоологии, 1979)
Results of studying new materials on Sciuridae, Myoxidae, Eomyidae, Zapodidae, Dipodidae, Spalacidae from Late Miocene (meotis) and Early Pliocene of the Odessa Black Sea area are generalized in this review (up to the genera) first for the European part of the USSR. The paper includes essays of the history of the above mentioned rodent families in the mentioned period of time. The two-stage prochoresis of the Asian forms to the southern boundaries of the Europen part of the USSR which occurred in the ancient meotis and at the finite stage of Pontian is shown.